PENGUKURAN KINERJA ORGANISASI NIRLABA DARI PERSPEKTIF BALANCED SCORECARD PADA RUMAH SAKIT UMUM HAJI SURABAYA - Widhiyaningrat, Wulan Ayu; Idayati, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to measure the performance and the benefit which has been obtained by using balanced scorecard method as the performance measurement instrument. The research object is Hajj General Hospital Surabaya. This research is qualitative approach; the data collection technique has been done by performing observation, interview, and documentation.Balanced scorecard consists of four perspectives i.e.: financial, customers, internal business process, growth and learning. The result of the research from the financial perspective on economy ratio shows that there is a decline in the performance which is uneconomical whereas the efficiency ratio shows that there is inefficient performance and the effectiveness ratio shows effective performance. The customer perspective shows a good result. Based on the perspective of internal business process, it shows that the performance is quite well whereas the growth and learning perspective from the employeesâ satisfaction shows the quite satisfactory value. Meanwhile, the retention of employee shows that there is a declination of the hospital in maintaining its employees.Keywords: Balanced Scorecard, Performance, Four Perspectives.